Adjusting Minimal Maintenance Margin Requirement When Price Limits Widening - 王明昌; 鄭揚耀; 陳宥榤; Ming-Chang Wang; Lee-Young Cheng; You-Jie Chen (My University, 2014)
本研究昌在探討台股放寬漲跌幅限制時，現行信用交易的整戶擔保維持率是否需要調整以確保授信機構的債權。本研究藉GARJI模型估計風險值，推估不同漲跌幅之最低擔保維持率臨界值，再以最低擔保維持率的上限值為基準，利用台股過去不同信心水準、風險程度、模擬投資人的投資組合，推估放寬漲跌幅時最低擔保維持率臨界值，同時以保障條數比較台指期與證券信用交易。實證結果發現：漲跌幅放寬為10%時，現行法定最低擔保維率120%對授信機構之債權保障可能有些微不足；另一方面，即時性的證券市場之信用交易保障程度是近似於期貨市場。本研究結果提供政策制定者，於價格限制放寬時，對信用交易有關整戶擔保維持率提供最適設定。

This study aims at to investigate whether the minimal maintenance margin requirement (MMMR) need to adjust considering sufficient safety of the credit trading when the regulators in Taiwan Stock Exchange widen the price limits. Based on different confidence interval, risks, and multiple simulations of portfolios, we estimate Value-at-Risk (VaR) by GARJI model to derive the MMMR threshold according to the upper bound of MMMR. Furthermore, as a key reference of index future in TAlFEX, we establish a credit security degree for standardizing to compare the difference between maintenance margin requirement in spots and future market. Our empirical results show that the MMMR at 120% could be slightly insufficient to secure claims under widening to reach 10% price limits. On the other hand, the credit security degree of instantaneous maintenance margin in spots market might approximate to futures market. This study provides the critical economical implicate for policy makers to set the optimal MMMR when the price limits widen.
股市漲跌幅放寬對信用交易之最低整戶擔保維持率之調整
Keywords: 價格限制; 最低擔保維持率; 風險值; Price Limits; Minimal Maintenance Margin Requirement (MMMR); Value-at-Risk (VaR)